1982
DOI: 10.1111/j.1365-2648.1982.tb00274.x
|View full text |Cite
|
Sign up to set email alerts
|

A clinical trial of a bead bed system for the prevention of pressure sores in elderly orthopaedic patients

Abstract: This paper summarizes the results of the trial of the Beaufort Bead Bed system designed to reduce the incidence and severity of pressure sores. Elderly orthopaedic admissions were allocated alternately to the Beaufort system and to the usual trolley, table and bed surfaces, and followed from admission to hospital until separation. The incidence of pressure sores was 15.6% in the 32 'trial' patients, which was significantly less than the 48.8% in the 43 'control' patients, as was the mean maximum diameter of th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2001
2001
2021
2021

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 49 publications
(10 citation statements)
references
References 0 publications
0
9
0
Order By: Relevance
“…In some prospective, randomized trials, use of pressure-reducing devices led to a lower incidence and severity of pressure ulcers than with a standard hospital mattress among orthopedic patients, 30,31 surgical and oncology patients, 32 intensive care patients, 33,34 and acute hospital patients. 35 Not all trials, however, showed a difference in preventing pressure ulcers in acute care [36][37][38] or in long-term care.…”
Section: Turning Every 2 Hours May Not Be Enoughmentioning
confidence: 99%
“…In some prospective, randomized trials, use of pressure-reducing devices led to a lower incidence and severity of pressure ulcers than with a standard hospital mattress among orthopedic patients, 30,31 surgical and oncology patients, 32 intensive care patients, 33,34 and acute hospital patients. 35 Not all trials, however, showed a difference in preventing pressure ulcers in acute care [36][37][38] or in long-term care.…”
Section: Turning Every 2 Hours May Not Be Enoughmentioning
confidence: 99%
“…A variety of materials are used for support surfaces, such as air-filled supports, water-filled supports, contoured or textured foam supports, and alternative foam mattresses or overlays [2]. As the surface materials differ significantly from each other, previous studies have not reached a definite conclusion on the effect of support surfaces on preventing pressure injury development [2,24,[26][27][28][29][30][31][32]. Furthermore, these studies have a high heterogeneity in study design, sample size, settings, and comparative standard hospital mattresses, which may also partially explain the heterogeneity in results.…”
Section: Discussionmentioning
confidence: 99%
“…Alternatively, foam mattresses or overlays, especially those with pressure redistributing characteristics, have become an increasingly popular method of attempting to reduce the development of pressure injuries without compromising patients' comfort [2,25]. However, the findings on the association between foam supports and the occurrence of pressure injuries are inconsistent, with some showing a decrease in the incidence of pressure injuries [26][27][28][29], some concluding no significant effect [30][31][32], and some presenting a slight increase in the development of pressure injuries [33] depending on various characteristics of the support surfaces, study design, settings, etc.…”
Section: Introductionmentioning
confidence: 99%
“…Incorrect randomisation method (randomisation based on participants' hospital numbers) Gebhardt 1996 Incorrect randomisation method Geelkerken 1994 Commentary Goldstone 1982 Incorrect randomisation method The study authors describe a random component in the sequence generation process, such as referring to a random number table, using a computer random number generator, coin tossing, shuffling cards or envelopes, throwing dice, drawing of lots.…”
Section: Low Riskmentioning
confidence: 99%